Effectiveness and safety of tenofovir alafenamide in chronic hepatitis B patients over 30 years old with positive hepatitis B virus DNA: a double-center retrospective study - Feng, Yinong; Zhou, Li; Shi, Shaoyuan; Wang, Zehong; Wang, Xuanxuan; Du, Fan (Frontiers in Medicine, 2025)
AimsThe aim of this study was to evaluate the effectiveness and safety of Tenofovir Alafenamide (TAF) in chronic hepatitis B (CHB) patients, particularly those aged 30–35 years or with baseline normal alanine aminotransferase (ALT) levels.MethodsA total of 191 patients were recruited, and their data were collected from two hospital in China from January 2017 to March 2023. Liver function and HBV-related indicators were measured at baseline, 48-week, and 96-week. The safety and effectiveness of TAF were evaluated in the high-age group (> 35 years) and the low-age group (30–35 years), as well as in the ALT-normal group (ALT < 1 × ULN) and the ALT-elevated (ALT ≥ 1 × ULN) group.ResultsTAF treatment for 48 weeks or 96 weeks could significantly improve the progression of hepatitis as evidenced by lower ALT, AST, and HBV DNA. TAF is still effective for patients aged 30–35 or those with normal ALT levels. Additionally, for CHB patients with baseline chronic kidney disease staging at stage 2 or below, 1–2 years of TAF treatment has minimal impact on their renal function.ConclusionTAF treatment significantly alleviated the progression of CHB patients over a 96-week follow-up period. TAF remains effective for younger patients or those with normal liver function, providing evidence for further expanding antiviral indications.